(untitled) (Al-Academy, 2023)
The research discussed the topic of the functional role of responsive materials in being elements of a functional transformation in the design of industrial products, based on the study of the structures of smart materials and their performance capabilities at the level of action and self-reaction that characterize this type of materials. Basic features of responsive materials have been identified to be elements of self-functional insertion into the industrial product design, which contributes to raising the efficiency and functional capacity of the industrial product and enhancing the ability of products to perform self-acting interactions in the structural structure of the material structure of the product and its ability to respond and interact with context variables. environmental. The responsive materials were classified into: electrical insulating materials, ceramics, piezoelectric polymers, shape memory alloys, shape memory polymers, thermoelectric materials, and electrical and magnetic fluids. And according to the cognitive propositions of research and discussion of methods and types of performance application of the characteristics of self-response materials in the design of industrial products that have the ability to self-response, a number of scientific conclusions were reached, which were, in their entirety, a scientific analysis of what and how of the design application of the characteristics of responsive materials in creating new functions in Industrial product design.